Karakteristik Batubara dan Batuan Sedimen Pembawanya, Formasi Talangakar, di daerah Lampung Tengah - Kusnama, Kusnama; Panggabean, Hermes (Indonesian Journal on Geoscience, 2009)
http://dx.doi.org/10.17014/ijog.vol4no2.20095The rock succession of coal bearing formation, situated in Lampung Tengah, occupies the basinal margin or the western part of South Sumatra Basin. Physiographically, the rock succession lies in the Palembang Zone which directly contacts with the southernmost Barisan Mountain Zone. The rock facies consists of conglomerate, and conglomeratic and quartz sandstones in the lower part, whilst the upper part comprises shale, claystone, mudstone, siltstone, and coal with coally shale and shaly coal intercalations. The rock facies of coal bearing unit is strongly believed to be part of the Oligo - Miocene Talangakar Formation deposited in a fluvial – paralic environment which further up section, it turns to be a sub-littoral deposit. The depositional environment strongly affected the coal characteristics and type. Stratigraphically, the rock unit is conformably overlain by the Early - Middle Miocene limestone unit and is intruded by the Middle – Late Miocene granodiorite. The basement of the Tertiary rock succession is metamorphics of the Gunungkasih Complex and the Cretaceous granitic rock. The normal fault controlling the area studied has a northwest - southeast direction and it caused the dip of coal trending north - east direction of 15º - 23º. The coal of the research area was deposited in wet forest swamp environment within a high to medium subsidence level. The coal is grouped to a high to low volatile bituminuous rank, included to a mature category.